A simplified transient technique for porosity and permeability determination in tight formations: Numerical simulation and experimental validation. Issue 3 (23rd October 2020) - Li, Zequan; Feng, Ruimin; Liu, Jun; Pandey, Rohit
Abstract: A simplified pulse decay method (PDM) with only a single downstream reservoir is proposed to replicate the in situ conditions for reservoir fluid flow, where the pore pressure at any location declines as production continues. The proposed PDM also allows determining the effective porosity and permeability for the core sample under replicated in situ conditions. A mathematical model is firstly established to closely represent the experimental design and verify the feasibility of the method. The analytical solutions of the model are derived to calculate the effective sample porosity and permeability. A series of experiments are then conducted under triaxial stress condition, and a detailed comparison is also made between the PDMs with a single upstream reservoir and a single downstream reservoir. The experimental results showed that accurate measurements on effective sample porosity and permeability can be achieved by the single downstream reservoir PDM due to its capability of better replicating the in situ fluid flow behavior, which extends the application of the transient technique. It is also found that the pore pressure along the sample changes linearly, and its gradient varies with time, indicating the applicability of the single‐reservoir PDMs in permeability determination. This method also lays a foundation for studying flow behavior when a second fluid phase evolves during pressure decline, which occurs in many reservoirs. Abstract : A simplified transient technique is proposed to simultaneously measure porosity and permeability of tight gas formations, and the influence of gas compressibility, gas compressive storage, and gas sorption on the measured permeability is investigated experimentally and numerically.